2018
DOI: 10.1111/psyp.13278
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dyspnea and threat of dyspnea on error processing

Abstract: Dyspnea (breathlessness) is a threatening and aversive bodily sensation and a major symptom of various diseases. It has been suggested to impair several aspects of functioning in affected patients, but experimental proof for this assumption is widely absent. Error processing is an important domain of functioning and has intensively been studied using electrophysiological measures. Specifically, the error-related negativity (ERN) has been suggested to reflect early performance monitoring and error detection, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 89 publications
(174 reference statements)
6
22
0
Order By: Relevance
“…Nevertheless, the present findings by LAWI et al [32], together with those from previous studies [24][25][26][27][28][29][30][31], have several important implications. First, they highlight that dyspnoea per se changes important higher brain processes, above the level of the brainstem respiratory oscillator required for normal and usually unconscious breathing.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…Nevertheless, the present findings by LAWI et al [32], together with those from previous studies [24][25][26][27][28][29][30][31], have several important implications. First, they highlight that dyspnoea per se changes important higher brain processes, above the level of the brainstem respiratory oscillator required for normal and usually unconscious breathing.…”
supporting
confidence: 64%
“…Although not directly measured by LAWI et al [32], several previous studies using different neuroimaging techniques have already demonstrated that experimentally induced dyspnoea activates brain networks, which are also involved in cognitive, affective and motor processing [40][41][42]. These activations during acute dyspnoea, especially if involving brain areas that are needed for both processing of dyspnoea as well as cognitive and motor functions, limit available brain processing capacities for simultaneous cognitive and locomotor performance [26,29,30]. This dyspnoea-cognition/locomotor interference is in line with previous findings on dual-task interference showing that the simultaneous engagement in two tasks diminishes performance in both tasks, especially when depending on shared brain networks [43,44].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted September 23, 2019. . https://doi.org/10.1101/19006684 doi: medRxiv preprint colleagues suggest that the threat of breathlessness may affect attentional processing by absorbing the available resources [20]. We assessed whether these findings could be replicated within the COPD population using an emotional Stroop task.…”
Section: Emotional Stroopmentioning
confidence: 99%
“…Sixty-four healthy participants were enrolled; four stopped during the sensitization procedure due to unbearable pain (two in experiment 1 and 2 in experiment 2). The final sample was composed of sixty participants: Twenty took part in experiment 1, (14 women, 6 men; median age 22 years, range 19-37), 19 in experiment 2 (15 women, 4 men; median age 22 years, range 18-40), 20 in experiment 3 (10 women, 11 men; median age 26, range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. None of the participants took part in more than one experiment.…”
Section: Participantsmentioning
confidence: 99%